Accessory titanomagnetite typomorphism of devonian granitoids in North-Western area of Rudni Altai - Konstantin Novoselov; Yuriy Turkin (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
Research relevance consists in determining the demand in mineral geochemical investigation of potential granitoid ore-bearing com plexes in Rudni Altai, embracing significant reserves of non-ferrous, noble and rare metals, which, in its turn, would expand the existing Russian mineral resources. Research target is to identify the distinctive accessory titanomagnetite as typomorphism characteristics of potential ore-bearing polyphase Aleysky-Zmeinogorsk granitoid complexes. Research methods in determining mineral chemical composition are: micro-sonde CAMEBAX-MICRO; electronic scanning microscope JSM-6510LV (Joel Ltd.) with energy-dispersive spectroscopy INCAEnergy350+. Research results include the following: initial detailed investigation of accessory magnetite of Aleysky-Zmeinogorsk granitoids and identification of two generations - early-magnetic titanomagnetite and post-magnetic titanomagnetite. The first of which is the decomposition-oxidation of magnetite-ulvospinel structure system. The following siderophile inclusion elements are predominate - Mn, V, Mg, Cr, Ge, while lithophylic elements - Al, Si, Y are less and chalcophylic elements are absent. The post-magmatic magnetite genesis was determined, being the result of titanomagnetite leaching via magmatogene hydrothermal solutions and further crystallization of magnetite, which, in its turn, derives the chemical behavior of titanomagnetite itself. In this case it characterizes low content or absence of Ti and other inclusion elements. The characteristic of V behavior was noted - in the final leucogranite phases magnetite contains more V than in early-magnetic titanomagnetite. Conclusion. Specific decomposition structure and titanomagnetite inclusion elements are typomorphic features of the basaltoid nature of granitoids. Specific potassic features of alkalinity, increased silica acidity and volatile activity during the final phase inhibit the possible V accumulation in titanomagnetite. Early-magnetic titanomagnetite is the mineral-concentrator V. This fact reflects the syngenetic enrichment of these melted elements and geochemical differentiation of Aleysky-Zmeinogorsk granitoids into Fe, Ti and V, as well as, Y and REE.